Traumatic injuries of the limbs in trauma-orthopedics: epidemiology, pathology, clinical presentation and management at Brazzaville University Hospital - Marius, Monka; Olivier, Ohoya Etsaka Terence; Albert, Ngatsé Oko; Armand, Moyikoua (International Journal of Research in Orthopaedics, 2020)
Background: The objective of the study was to report the experience in the management of traumatic injuries of the limbs. Methods: This was a retrospective descriptive study involving 342 patients managed in our department from January 2017 to December 2018. Study variables included epidemiology, clinical presentation and management. Open fractures were classified according to Cauchoix Duparc classification. Results: The study population included 241 males (70, 47%) and 101 females (29, 53%). The mean age was 44, 7 years (18 and 96 years). The lower limbs were involved in 292 patients (85, 4%); the upper limb in 50 patients (14, 6%). Surgical treatment was achieved in 305 patients and orthopedic in 37 patients. The average hospital stay was 35 days for patients managed surgically and 2 months for patients managed orthpedically. A 6 years follow up revealed 9 cases of osteitis on external fixators; 4 cases of aseptic non-union and 13 cases of moderate knee stiffness. Conclusions: Traumatic injuries of the limbs represent a major problem encountered in our daily practice. The predominance of pelvic limb fractures in most cases is due to road accidents. To prevent these issues actions should be taken such as upgrading the infrastructures and setting a health insurance system for all in order to ensure early and adequate care for all.